Unraveling the mediating role of plant color and familiarity on children’s mood in urban landscape - Han Sheng; Xu Li; Shucai Zeng (Journal of Asian Architecture and Building Engineering)
An important element of urban landscapes is various plants, and contact with urban landscapes can promote children’s positive mood and mental health. However, few studies focus on Asian school-aged children’s mood for different urban landscapes and the factors shaping them. This study attempted to understand the variables, including plant color, familiarity, and viewing distances (setting 0 m and 2 m), using 150 landscape scenes (68 flowering plants, 50 exotic plants, and 32 foliage plants), on the effects of the landscape preferences and mood states of 119 school-aged children (55 boys and 64 girls). Then, using partial least squares path modelling analysis to display the gender difference in children’s color perception, landscape preferences, and mood states. The results show that: (1) Plant color richness, familiarity, and the proportion of non-green parts of scenes positively affected children’s mood states. (2) Flowering plants are more likely to produce positive moods than those of exotic plants and foliage plants. (3) Plant color richness and familiarity significantly and positively correlated with children’s mood states and landscape preferences. (4) Notably, gender differences exist in children’s landscape preferences and mood states. This study underscores the importance of plant color collocation in child-friendly landscapes and considers the gender differences in urban landscape policy decisions. Besides, adding flowering plants and native plants in urban landscapes may potentially enhance children’s mood state and urban green space utilization rate.